Irrational Numbers with Generalized Bounded Partial Quotients - Kaikeaw, Ratchanai; Hengkrawit, Charinthip (Thai Journal of Science and Technology, 2013)
<!--[if gte mso 9]> <![endif]--> Abstract The definition of irrational numbers with generalized bounded partial quotients is defined. We will investigate some relation between irrational numbers with bounded partial quotients in simple continued fraction and in generalized continued fraction. Furthermore, using three distance theorem of Slater, we also find the result of three distance theorem for generalized continued fraction in some kind of sequence. Keywords: continued fraction; bounded partial quotients; three distance theorem. <!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE TH <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->